Enhancement of gas storage and separation properties of microporous polymers by simple chemical modifications. Issue 2 (1st June 2021) - Rochat, Sébastien; Tian, Mi; Atri, Ria; Mays, Timothy J; Burrows, Andrew D
Abstract: Owing to their large surface area and good solvent processability, polymers of intrinsic microporosity (PIMs) have been widely investigated for gas storage and separation processes. In this article, we show how chemically modifying the polymers can fine-tune their properties for specific, targeted applications. We find that converting the archetypal microporous polymer PIM-1 into a polycarboxylate salt enhances its separation capabilities for H2 /CO2 mixtures (relevant to hydrogen production), whereas appending multiple amine groups significantly improves gas separation properties for N2 /CO2 mixtures (relevant to flue gas treatment). Adsorption-based separation processes have received less attention than size-sieving processes in porous polymeric materials, however they could provide a suitable alternative technology to energy-intensive separation processes such as cryogenic distillation. We also report the hydrogen storage properties of the modified polymers, which we find to depend on the chemical modification carried out. By coupling the simplicity of the proposed chemical modifications with the scalability and porous properties of PIMs, we provide a blueprint to create new multifunctional materials with adapted properties for targeted applications.